A hierarchical nickel–carbon structure templated by metal–organic frameworks for efficient overall water splitting. Issue 9 (3rd July 2018) - Sun, Hao; Lian, Yuebin; Yang, Cheng; Xiong, Likun; Qi, Pengwei; Mu, Qiaoqiao; Zhao, Xiaohui; Guo, Jun; Deng, Zhao; Peng, Yang
Abstract : High efficiency overall water splitting enabled by a hierarchical Ni–C structure derived from 2D MOF sheets without heteroatom doping. Abstract : The development of high-performance and cost-effective catalysts for the hydrogen and oxygen evolution reactions is key to efficient electrocatalysis of water, which offers a promising solution to convert and store those green but unsteady energies. Herein, we report a hierarchical nickel–carbon composite, fabricated by directly growing sheet-like Ni–MOFs on commercial nickel foam prior to high-temperature annealing, as a highly efficient bifunctional catalyst. This composite shows remarkable catalytic activities for both the hydrogen and oxygen evolution reactions in an alkaline electrolyte, affording a current density of 10 mA cm −2 at an overpotential of 37 mV for the HER and 265 mV for the OER. Furthermore, an electrolyzer employing the composite as a bifunctional catalyst in both the cathode and the anode delivers a current density of 35.9 mA cm −2 at a cell voltage of 1.60 V with extended stability, which is even superior to the integrated Pt/C and RuO2 counterparts. This excellent performance is believed to be a result of a concerted synergy due to its hierarchical structure, enabling excellent reaction kinetics. Further ex situ XRD and XPS analyses reveal that while metallic nickel is responsible for the HER, Ni nanoparticles with an oxide shell encapsulated in graphitic carbon are the OER catalytically-active sites formed in situ .